(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study of decision making for children to choose ballet in Chonburi province Conclusion Marketing mix factors (7P’s) Product Price Distribution channels Marketing promotion Personnel In the creation and presentation of physical characteristics Process Parents pay more attention to the selection of ballet schools at a high level, and the results of the regression test show that the marketing mix (7P’s) influences the decision making process of parents in sending their children to school. Ballet teaching in Chonburi As for the different personal factors affecting parents’ decisions in sending their children to a ballet school in Chonburi, which is different. ANOVA statistical test Found that personal factors in terms of sex, age, education, occupation, and income are different. Has no effect on parents’ decision to send their children to a ballet school in Chonburi.